Adopting Sustainability: The Role of Motivation and Intention to Forming Green Behavior - Yudanto, Khrisna Vembri; Martdianty, Fanny (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: In the midst of increasingly worrying environmental conditions, various actions are needed from both individual and organizational sides in determining their behavior. All behavior is believed to have an impact on the environment, depending on the behavior itself. It was discovered that employee green behavior (EGB), was used as an instrument to realize corporate sustainability.Purpose: This research aims to determine the influence of employee knowledge and awareness on EGB, which is mediated by the factors of green motivation and behavioral intentions.Design/methodology/approach: This research uses primary data taken from a survey from a state-owned company in Indonesia running in the energy sector, disguised as XYZ Company. The sample used was 422 employees. The data analysis was conducted by structural equation modeling (SEM) with Lisrel 8.80.Finding/result: This research found that green motivation and behavioral intentions were proven to significantly mediate the relationship between employee knowledge and awareness on employee green behavior. Conclusion: This research has deep implications in enriching the perspective of implementing environmentally friendly behavior in the business environment and strengthening managerial management by providing comprehensive considerations for management in realizing environmentally friendly business processes as a whole, especially in the field of human resource management.Originality/value (State of the art): This research fills the empirical gap by providing research in the energy sector and increasing the number of samples used from previous research. Keywords: behavioral intention, green behavior, green motivation, knowledge and awareness, sustainability